The impact of sleep disorders on the course of hypertension - A. V. Budnevsky; E. S. Drobysheva; R. E. Tokmachev; N. V. Rezova (Лечащий Врач)
The article is a review of the literature, which presents the results of clinical studies on the effect of sleep disorders on the course of hypertension and the relationship between sleep duration and risk of occurrence and progression of the disease. In addition, the mechanisms of melatonin on the body and related effects are described.